Giant days Volume eight - Allison, John, 1976-; Allison, John, 1976- (Boom! Studios, 2018)
"Its the end of second year for best mates Susan, Daisy, and Esther, and cracks are appearing in the foundation of this unshakeable trio. Between (irritating) new loves, (secretive) old loves, (unlikely) new friendships and (terrible) old houses, theyll be lucky to make it to third year alive!"--Back cover.